2022
DOI: 10.37647/0132-2486-2022-112-1-52-55
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Patients after Conservative Treatment of Adolescent Idiopathic Scoliosis

Abstract: Summary. Relevance. Health-related quality of life (HRQoL) is an important indicator of the treatment. Quality of life consists of functional, physical, emotional, social and spiritual states [1], and therefore has become a leading criterion in many researches, along with physical and economic factors. In the course of its development, the concept of quality of life has been correctly indicated as a parameter of the result in the recommendations of many medical societies [2]. Objective: to assess the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a study conducted by Vasiliadis and Grivas, 32 girls diagnosed as adolescent idiopathic were treated conservatively, including physiotherapy, and the changes in the subjects' quality of life and pain were investigated. Significant changes in pain scores and quality of life measures and physical functionality were reported at two-year follow-up (24). In their study, Çolak et al (25) observed a higher increase in the quality of life with conservative treatment than after surgical treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In a study conducted by Vasiliadis and Grivas, 32 girls diagnosed as adolescent idiopathic were treated conservatively, including physiotherapy, and the changes in the subjects' quality of life and pain were investigated. Significant changes in pain scores and quality of life measures and physical functionality were reported at two-year follow-up (24). In their study, Çolak et al (25) observed a higher increase in the quality of life with conservative treatment than after surgical treatment.…”
Section: Discussionmentioning
confidence: 89%